Educational Crimination for Minor Children Who Complete Criminal Offices in Indonesia - Muhammad Firman Piko Prayogo; Yopik Gani (Budapest International Research and Critics University, 2022)
Children have the right to the protection of their constitutional rights, such as guaranteeing laws and regulations that are pro-child rights. Because the direction of legal policy aims to make law a rule that provides protection for the rights of citizens and guarantees the lives of future generations. The formulation of the problem in this research is How is the educative punishment system for children as criminals in Indonesia today? and 2. How is the educative punishment system in the future appropriate for children as perpetrators of criminal acts?. The research method used is this method is used juridical normative emphasizing on the science of law and the study of legal rules that apply in society related to the criminal system against children as perpetrators of criminal acts. The specifications used in this research are analytical descriptive, because this research is expected to obtain a clear, detailed and systematic picture. The legal materials used are primary, secondary, and tertiary legal materials. Analysis of qualitative descriptive legal materials. The results showed that child protection law is a legal subsystem and the purpose of criminal law, which includes a basic understanding of the principles of criminal law such as territorial principles, active personal principles, passive personal principles, universality principles, fictitious principles, and others. There are two legislative steps taken to protect children involved in criminal acts, namely Law Number 11 of 2012 concerning Juvenile Courts and Law Number 12 of 1995 concerning Corrections.An educational punishment system that is appropriate in the future for children as perpetrators of criminal acts is not given criminal sanctions by placing children in prison. The provision of educational sanctions must be the main consideration for judges in imposing sanctions, such as placing children in special schools that can place children as individuals who must receive guidance both morally and intellectually. The government should have started to seriously implement Restorative Justice, because this is an alternative for juvenile justice in Indonesia that prioritizes a welfare approach and a justice approach.